3.4(-3.8z+1.2b-3.3)=

Simple and best practice solution for 3.4(-3.8z+1.2b-3.3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3.4(-3.8z+1.2b-3.3)= equation:


Simplifying
3.4(-3.8z + 1.2b + -3.3) = 0

Reorder the terms:
3.4(-3.3 + 1.2b + -3.8z) = 0
(-3.3 * 3.4 + 1.2b * 3.4 + -3.8z * 3.4) = 0
(-11.22 + 4.08b + -12.92z) = 0

Solving
-11.22 + 4.08b + -12.92z = 0

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add '11.22' to each side of the equation.
-11.22 + 4.08b + 11.22 + -12.92z = 0 + 11.22

Reorder the terms:
-11.22 + 11.22 + 4.08b + -12.92z = 0 + 11.22

Combine like terms: -11.22 + 11.22 = 0.00
0.00 + 4.08b + -12.92z = 0 + 11.22
4.08b + -12.92z = 0 + 11.22

Combine like terms: 0 + 11.22 = 11.22
4.08b + -12.92z = 11.22

Add '12.92z' to each side of the equation.
4.08b + -12.92z + 12.92z = 11.22 + 12.92z

Combine like terms: -12.92z + 12.92z = 0.00
4.08b + 0.00 = 11.22 + 12.92z
4.08b = 11.22 + 12.92z

Divide each side by '4.08'.
b = 2.75 + 3.166666667z

Simplifying
b = 2.75 + 3.166666667z

See similar equations:

| 7/98 | | 987whcsdg=7 | | 5s-r+7r-6s= | | x/4+6=x+12 | | 51.56-29.28x=47.78-68.82 | | 9xd=4 | | 1x+1=1x-1 | | 11p-6c-7c+9p= | | 2r-3s+5s-r= | | 1/2t+6=5 | | 4(+2)=14-2(3-4) | | X/4-2/5=7/20 | | .1234x+4.921x=94x+6 | | 5x-7/2=10x+3/2 | | 8x+9=4x-8 | | 6.4=0.8m | | -6x+3=8x-4 | | 7(2x-3)=14x-21 | | 5+8n=-67 | | 2y-5-5y+3= | | .1234x+4.921x=94x | | x/15-3=4 | | 7t+4u+3t-2u= | | 16.67(x+4)=4x-10(2-x)-7 | | r-8=17 | | 3.50c+5.50c+6=51 | | 3/5q=15 | | 7x-6+5x=78 | | -8=7-n | | x^2-10x=-18 | | 3/4x-3/4=9 | | 0.2x+1.4=0.9x-1.4 |

Equations solver categories